ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN DI PT UNILIVER TBK TAHUN 2020-2024 - Timoteus Kesogihan; Rina Malahayati; Ardi Hirmansa (Jurnal Ekonomi, Manajemen dan Akuntansi, 2026)
This study examines the implementation of environmental accounting at PT Unilever Tbk, with a focus on the management of waste. The objective of the research is to assess how the company recognizes, measures, presents, identifies, and discloses environmental costs and to evaluate the alignment of these practices with the framework proposed by Saputra and Martini. A descriptive qualitative method was employed, utilizing both primary and secondary data. Primary data were obtained through direct observations and interviews with personnel responsible for environmental management, providing detailed insights into operational procedures. Secondary data were collected from sustainability reports, environmental cost reports, and company documentation, offering historical and contextual information regarding PT Unilever’s environmental initiatives. The findings indicate that PT Unilever has effectively managed liquid and air waste, with recognition, measurement, and presentation of environmental costs aligned with Saputra and Martini’s theoretical framework. Costs are recorded in monetary terms and presented in financial statements under general and administrative expenses. However, the study identifies gaps in the identification and disclosure of environmental costs. The company has not fully classified costs into prevention, detection, internal failure, and external failure categories, nor provided separate disclosure in financial statements. This suggests that while operational and accounting practices are well-established, improvements in transparency, standardization, and comprehensive reporting are necessary to enhance stakeholder accountability and support sustainable business practices